Casebook of Sherlock Holmes. - Doyle, Arthur Conan, 1859-1930.; Irwin, Don (Santa Rosa, Calif., Classic Press, 1968)
The adventures of Sherlock Holmes and Dr. Watson are recounted in selected short stories and in two longer works "A Study in Scarlet" and "The Hound of the Baskervilles."
Keywords: Holmes, Sherlock -- Fiction; Detective and mystery stories, English; Children's stories, English; Mystery and detective stories